The Correlation between English Speaking Skill and Self-Confidence among Eleventh Grade Students at SMA Negeri 1 Alasa - Lase, Pintauli; Laoli, Adieli; Harefa, Afore Tahir; Telaumbanua, Yasminar Amaerita (Universitas Muhammadiyah Mataram, 2025)
This research aims to find out if there is a significant correlation between English speaking skill and self-confidence among grade XI students in a senior high school. The research started because in class, some students speak English well but feel shy in public, while others look confident but has low speaking skills. This research used a quantitative method with a correlational design. The sample was 35 students from class XI Ki Hadjar Dewantara. Data were collected through a speaking test to measure English speaking skill and a Likert scale questionnaire for self-confidence. Data were analyzed using parametric tests, including normality test, Pearson Product Moment correlation, and simple linear regression in SPSS version 25. All instruments were tested for validity and reliability before use. The result showed the correlation value (r) was 0.022 with a significance of 0.901 (>0.05). This means there is no significant correlation between English speaking skill and self-confidence. Field observations also showed that students who speak well are not always confident, and confident students do not always have good speaking skills. It can be concluded that speaking skill and self-confidence are separate aspects and need to be developed on their own. This research may help teachers and researchers plan better English learning strategies.